2008
DOI: 10.1037/1065-9293.60.1.42
|View full text |Cite
|
Sign up to set email alerts
|

Development of a model of the feedback process within executive coaching.

Abstract: Recent literature concerning executive coaching consistently points out the need for a better conceptual understanding of the process of coaching. The current paper addresses this need with an emphasis on the role of feedback in executive coaching. Several existing models of the coaching process mention feedback as an important element, but none expand on the role and function of feedback in executive coaching relationships. This paper builds on several existing models of executive coaching and integrates Lond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
70
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(77 citation statements)
references
References 27 publications
3
70
0
2
Order By: Relevance
“…Although at least one or two formal feedback reviews are usually required in the formal performance management process, the reality is that informal, continuous feedback is the most important and powerful feedback that can be given. Both the research and practice literatures have advocated that feedback be provided immediately following effective or ineffective performance (e.g., Gregory, Levy, and Jeffers, 2008; Kirkland & Manoogian, 2007; Wexley, 1986). The Gregory et al (2008) literature review specifically highlights the importance of continuous feedback to help employees make real‐time alterations in their behavior, enabling them to perform their work more efficiently and effectively.…”
Section: Interventions To Improve Manager–employee Communication and mentioning
confidence: 99%
“…Although at least one or two formal feedback reviews are usually required in the formal performance management process, the reality is that informal, continuous feedback is the most important and powerful feedback that can be given. Both the research and practice literatures have advocated that feedback be provided immediately following effective or ineffective performance (e.g., Gregory, Levy, and Jeffers, 2008; Kirkland & Manoogian, 2007; Wexley, 1986). The Gregory et al (2008) literature review specifically highlights the importance of continuous feedback to help employees make real‐time alterations in their behavior, enabling them to perform their work more efficiently and effectively.…”
Section: Interventions To Improve Manager–employee Communication and mentioning
confidence: 99%
“…Years of research studies have shown that feedback immediately following a performance event has the most impact on performance. Done right, it accomplishes three things (Gregory, Levy, & Jeffers, 2008;Kirkland & Manoogian, 2007;Murphy & Cleveland, 1995): r strengthens the relationship between the recipient and the feedback provider, r maximizes a positive outcome, and r develops the recipient.…”
Section: Inspire: Link Each Individual's Work To the Organization's Mmentioning
confidence: 99%
“…Specifically, related to our previous discussion about the effect of interpersonal dynamics on PA, we think a productive PM process requires creating and maintaining a nonthreatening organizational social environment that facilitates ongoing communication and feedback among employees. Pulakos et al (2015) have pointed out a consistent stream of empirical evidence showing that informal, continuous feedback that occurs on a day-to-day basis in such an environment (and preferably immediately following effective or ineffective performance episode; Gregory, Levy, & Jeffers, 2008) is much more likely to create real-time alterations in employees' job performance behaviors than are intermittent formal feedback sessions. Compared with formal feedback, informal feedback occurs naturally and is perhaps unexpected; ideally, it involves full engagement in feedback discussions that require genuine interpersonal interaction and accountability for both parties who are sending, receiving, or exchanging feedback.…”
Section: Create An Environment For Open Communicationmentioning
confidence: 99%
“…Related to this, recent theoretical models on learning, development, and PM in organizations (e.g., Gregory et al, 2008;London & Smither, 2002) have focused on a construct called feedback orientation, a multidimensional trait defined as one's general receptivity to feedback information (London & Smither, 2002). Although research on feedback orientation to date has largely consisted of theoretical propositions (e.g., London & Smither, 2002) or scale development and validation studies (Linderbaum & Levy, 2010), in recent empirical work, Dahling, Chau, and O'Malley (2012) tested a model of a broader context for feedback orientation, in which employees' perceptions of the supervisor feedback environment had a positive, moderate effect on feedback orientation, which in turn had a positive, moderate effect on active feedback inquiry behavior.…”
Section: Create An Environment For Open Communicationmentioning
confidence: 99%